2002
DOI: 10.1074/jbc.m208418200
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Activators Differ in Their Abilities to Control Alternative Splicing

Abstract: Promoter and enhancer elements can influence alternative splicing, but the basis for this phenomenon is not well understood. Here we investigated how different transcriptional activators affect the decision between inclusion and exclusion (skipping) of the fibronectin EDI exon. A mutant of the acidic VP16 activation domain called SW6 that preferentially inhibits polymerase II (pol II) elongation caused a reduction in EDI exon skipping. Exon skipping was fully restored in the presence of the SW6 mutant by eithe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
153
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(164 citation statements)
references
References 35 publications
(57 reference statements)
10
153
1
Order By: Relevance
“…However, the number of homologous genes of human and mouse with conserved alternatively included exons is restricted, because genomewide investigation showed that the alternative exon inclusion comprises only approximately 15% of all alternative splicing events in contrast to exon skipping, which amounts to 48% approximately. 4 In addition, there are often inconsistent data concerning the classification of alternative cassette exons as skipped or included, for example, present or absent in the predominant transcript. Several genome-wide comparisons of expressed sequence tags or full-length cDNA clones with the genomic draft of human and mouse have been carried out to investigate the extent of alternative splicing in the respective genome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the number of homologous genes of human and mouse with conserved alternatively included exons is restricted, because genomewide investigation showed that the alternative exon inclusion comprises only approximately 15% of all alternative splicing events in contrast to exon skipping, which amounts to 48% approximately. 4 In addition, there are often inconsistent data concerning the classification of alternative cassette exons as skipped or included, for example, present or absent in the predominant transcript. Several genome-wide comparisons of expressed sequence tags or full-length cDNA clones with the genomic draft of human and mouse have been carried out to investigate the extent of alternative splicing in the respective genome.…”
Section: Discussionmentioning
confidence: 99%
“…1 -3 Interestingly, also the promoter seems to play a crucial role in alternative splicing. 4 Several isoforms can be generated by alternative splicing through cassette exon events (ie exon skipping or exon inclusion), exon and intron isoform events (ie use of alternative 3 0 or 5 0 splice sites) and intron retention. 2,3,5 We are interested in the regulation of alternative cassette exon events, a cassette exon being one included or excluded from the transcript.…”
Section: Introductionmentioning
confidence: 99%
“…Microscopic observations revealed that splicing factors are recruited to sites of active transcription (Jiménez-García and Spector 1993), and that introns can be detected only in proximity of the original gene (Zhang et al 1994), suggesting that intron removal takes place at, or in the immediate vicinity of, sites of transcription. In addition, functional studies in vivo demonstrated that promoter sequences can affect both constitutive splicing efficiency (Rosonina et al 2003) and the alternative splicing pattern of the transcript (Cramer et al 1997;Kadener et al 2002;Nogues et al 2002), as well as modulate the effect of protein factors involved in splicing regulation (Cramer et al 1999). These and other results suggest that the molecular events that underlie integration of transcription and processing take place within, or at least involve, the RNA polymerase II (RNAP II) transcription elongation complex.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence has accumulated in recent years for an important role of transcription in regulation of splicing 44 . Promoter structure 45 and association with transcription factors 46 and coregulators 47 have been demonstrated to be capable of strongly influencing patterns of alternative splicing through as-yet undefined mechanisms that are independent of transcriptional efficiency. As the transcriptional control sequences in retroviruses are located primarily within the LTR, and most importantly in the U3 region, the LTR mutations we identified may alter the extent to which the viral transcript is spliced by modulating interactions with components of the transcription machinery.…”
Section: Discussionmentioning
confidence: 99%